The relative distribution (percentage) proportions of various hormone producing cells in different regions of pars distalis adenohypophysis from buffalo of different phases of reproductive cycle - Khan, Massarat; Saigal, R P; Sethi, R S (The Indian Journal of Animal Sciences, 2012)
The percent distribution of different hormone producing cells of buffalo were studied in the paraffin sections of 52 pars distalis adenohypophysis cerebri of either sex aged 1 week to adult. The sections were stained to demonstrate GH, PRL, TSH, FSH and LH/ICSH cells with differential staining of the chromophils which comprised 40.32 ± 2.29%, 22.20 ± 1.61 %, 17.09% ± 0.82 %, 12.02 ± 1.19% and 8.36% ± 0.64% of population, respectively, whereas distribution of GH cells was maximum in zona tuberalis and rostral region, the PRL and LH were maximum in the ventral region, TSH in the caudal region and FSH cells in the central region of pars distalis. In adults, the males had higher proportions of GH (45.38%) and LH (12.76%) cells and lower proportions (14.08%) of PRL cells than those of females (38.31 %, 8.03% and 24.97%, respectively) in follicular phase. The LH cell proportions were higher (10.88%) during luteal phase. During pregnancy the GH cell proportions were maximum (48.25%) in early stages and PRL and FSH cells were maximum (27.60% and 18.41 %, respectively) after 3 months of pregnancy. The TSH and LH cells were maximum (23.32% and 28.06%, respectively) at 3 months pregnancy whereafter they decreased. With the advancement of pregnancy, the FSH and LH cells continued to decrease and increase, respectively, up to 3 months of pregnancy but thereafter while FSH cells increased and LH cells decreased both accounting to nearly same proportions.